If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x-2)=x+7+4x
We move all terms to the left:
3(3x-2)-(x+7+4x)=0
We add all the numbers together, and all the variables
3(3x-2)-(5x+7)=0
We multiply parentheses
9x-(5x+7)-6=0
We get rid of parentheses
9x-5x-7-6=0
We add all the numbers together, and all the variables
4x-13=0
We move all terms containing x to the left, all other terms to the right
4x=13
x=13/4
x=3+1/4
| x/10+97=117 | | 6x-4=12x+8 | | x/5+209=229 | | 6x+5x−9x−5=7 | | (7x+3)^2-21=0 | | {7x}{8}-3={23}{4} | | 10+7p=3(1+2p) | | 8–2x=22 | | 8y−6=5y+9 | | -1-2x=-5x+20 | | 1-5x+2=-2 | | 6/(5x+3)=0 | | x-833/4=23 | | 850-s=110 | | 2(x-10=60) | | 5x-4+12=6x+3 | | 7n-9n=7 | | 644/x=23 | | -97=3(1-6n)-7n | | 36=2(-2+20x) | | 33x=66+22x+6x | | 9x+5=13x | | 3x²+1=28 | | 31-c=4 | | -4-3n=1/2 | | 55-x=37 | | -7.|6-x|=24+2.5 | | m+(m-1)=7 | | 10=4x-5-2x+15-2x | | 2(3p-7)=22 | | 9x+5=13x=159 | | 1+5^x+2=0 |